Upaya Mempertahankan Bersihan Jalan Napas Pada Anak Dengan Tuberkulosis Paru - Syifa Ningtias Firnanda, Nurul; , Siti Arifah,S. Kp., M. Kes (2017)
Background : Tuberculosis is an infectious disease caused by tuberculosis mikrobacterium, which these microorganisms are aerobic, ie, like areas with high oxygen content, so that tuberculosis is more common lung organ. inflammatory reaction and phagocytosis against tuberculosis microbacterium causes the accumulation of exudate in the alveoli. Sputum that is not removed can lead to clearance of airway becomes ineffective, so that the oxygen supply will be disrupted and may result in cyanosis, fatigue, apathy and weakness. Objective : provide an overview of the application of nursing care in order to maintain airway clearance in children with pulmonary tuberculosis. Methods : the methode used is based on case studies of nursing care in children with pulmonary tuberculosis. Data obtained based on the result of a physical examination, observation of the environment around the home, direct interviews with patients and families,data prevalence of the disease in territory Polokarto and some reference books journals associated with pulmonary TB Disease. Implementation using five process includes assessment, establishing nursing diagnoses, interventions implementation and evaluation . Result : Patients were able to eject sputum, respiratory rate within normal limits, the patient's family is able to take action on the issue of clearance of airway independently. Conclusion : nursing actions that can be performed on patients with airway clearance ineffectiveness problems can be done by providing a simple inhalation and chest physiotherapy and continued with an effective cough. If the effective pediatric patients cough hard to do, can be a way to position patients with posterior basal segments